Design of a 2DOF Vibrational Energy Harvesting Device - Jang, S. -J.; Rustighi, E.; Brennan, M. J.; Lee, Y. P.; Jung, H. -J. (SAGE PUBLICATIONS LTD, 2011)
A novel design method for a 2DOF energy harvesting device is studied. The energy harvesting device is modeled as a rigid body supported by two parallel sets of springs and dampers. The impedance expression for the model has been developed by utilizing the concept of the inerter. The proposed design method deals with tuning two resonant peaks and equalizing the harvested power at those frequencies. As a result, the proposed energy harvesting device is particularly effective at two frequencies and has increased bandwidth as well as reduced size and weight in comparison with previous SDOF devices. A numerical design example is provided to show effectiveness of the proposed method.
Keywords: GENERATOR; MICROSYSTEMS; NETWORKS